PERANCANGAN UI/UX PADA APLIKASI FLAVOUR FOG MENGGUNAKAN PENDEKATAN USER CENTERED DESIGN - Frederick Alexander; Arianti; Syamsul Bahri (STMIK KHARISMA Makassar, 2022)
This study was conducted to determine whether the User Centered Design approach can build a better User Interface and User Experience on the Flavor Fog application so that it can meet the needs and desires of users. The method used is the System Usability Scale to determine the score of the application. The score obtained before the design was carried out was 70.8 which entered category C, while after designing using the User Centered Design approach, a score of 81.1 was obtained which entered category A. From these results it can be seen that there is an upgrade in the Flavor Fog application, so that it can be concluded that the application design using a User Centered Design approach with measurements using the System Usability Scale, can produce a User Interface and User Experience design that is in accordance with the needs and desires of the user.